EVALUATION OF BLUE GREEN ALGAE GROWN UNDER DIFFERENT pH CONDITION FOR BIOFUEL PRODUCTION - SUNITA SHARMA, E. P. LAL,; K.P.RAO, (International Journal of Pharma and Bio Sciences, 2015)
Blue green algae was isolated from fresh water bodies of Allahabad region, Yamuna River, India to produce biodiesel. Based on rate of growth in cultural media and morphological characters and biomass production, 8 colonizing blue green algae isolates were selected for the further biofuel production work. To further narrow down the number of isolates, the carbonic anhydrase enzyme assay was used as biochemical marker for identifying high CO2 fixation or hydrocarbon accumulation in the isolated colonizing blue green algae. Based on carbonic anhydrase enzyme assay of selected algal isolates, three potential high CA activity colonizing blue green algae (BIOLBG-6, BIOLBG-7 and BIOLBG-8) were selected. The algal growth was investigated in liquid media of BG-11 for 21 days and the growth was calculated in gram biomass per litre using different pH (5 to 9) condition by taking absorbance using Spectrophotometer at a wavelength of 680nm..The best growth of biomass was seen in pH 8 for blue green algae. For 0.15483 ml/g D.W. Biomass blue green algae 3 ml of methyl ester (biodiesel) was formed.